Psychosocial wellbeing and risk perception of older adults during COVID-19 pandemic in Nigeria: perspectives on the role of social workers - Rahman, Farah Naz; Iwuagwu, Anthony Obinna; Ngwu, Christopher Ndubuisi; Kalu, Michael Ebe; Kasherwa, Amani; Tasnim, Anika; Chowdhury, Mohamman Rocky Khan; Rashid, Mamunur; Kader, Manzur (Frontiers in Psychiatry, 2025)
BackgroundThe COVID-19 pandemic presented a ‘double-edged sword’ for older adults: not only were they more susceptible to the virus, but its broader consequences also exacerbated other challenges, particularly those related to psychosocial well-being. Limited evidence exists on how older adults perceive the pandemic and its impact on their well-being and the role of social workers in addressing these challenges, particularly in resource-limited settings like Nigeria.AimThis study explored older adults’ perceived risks regarding COVID-19, its impact on their psychosocial well-being, and the role of social workers in addressing these challenges in Nigeria.MethodsA phenomenological and exploratory research design was used. In-depth interviews (IDIs) were conducted with 16 older adults and 4 social workers in Onitsha metropolis, Anambra State, Southeast Nigeria. Data were analyzed through reflexive thematic analysis.ResultsThe findings revealed that the COVID-19 restrictive measures negatively impacted the psychosocial well-being of older adults, where social isolation, lack of support, the inability to engage in wellbeing activities, and emotional trauma collectively contributed to a significant decline in their mental and emotional health. Additionally, widespread misconceptions about the origin of COVID-19 led to reluctance in adopting preventive measures. While social workers provided some awareness and counselling sessions, their involvement was limited. Social workers were not recognized as part of the frontline response team, and their efforts were primarily constrained by governmental and institutional neglect.ConclusionThe findings highlight the need for policy initiatives to enhance social workers involvement in strengthening the psychosocial resilience of older adults and addressing misconceptions during public health emergencies. Comprehensive strategies are essential for safeguarding the psychosocial well-being of older adults in future pandemics or similar crises.